2022
DOI: 10.1111/1756-185x.14490
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patients with antiphospholipid syndrome subsequently COVID‐19 vaccinations: A retrospective cohort study

Abstract: The aim of this study is to evaluate development of side effects, thrombotic or obstetric complications in our antiphospholipid syndrome (APS) patient group, after vaccination against coronavirus disease 2019 (COVID‐19). A cohort was formed from patients who have previously been followed up with a diagnosis of APS. The patients of the cohort were evaluated retrospectively to find out if they were vaccinated with CoronaVac and/or BNT162b2 vaccines which are being used in our country. To evaluate the side effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In the present study, no thrombotic events or flares of APS were observed in any of the 35 patients with APS included in the study up to 3 months of follow up who had received mRNA or inactivated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine. 1 A limitation of this study was that only about one-half of the cohort of APS patients followed up at this center could be contacted for this study. Therefore, selection bias or survivorship bias cannot be excluded.…”
Section: Sars-cov-2 Vaccination Appears To Be Safe In Antiphospholipi...mentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, no thrombotic events or flares of APS were observed in any of the 35 patients with APS included in the study up to 3 months of follow up who had received mRNA or inactivated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine. 1 A limitation of this study was that only about one-half of the cohort of APS patients followed up at this center could be contacted for this study. Therefore, selection bias or survivorship bias cannot be excluded.…”
Section: Sars-cov-2 Vaccination Appears To Be Safe In Antiphospholipi...mentioning
confidence: 99%
“…The identified studies are summarized in Table 1. 1,[4][5][6][7][8][9][10][11][12] Six studies assessed the safety of COVID-19 vaccination in more than 1300 patients with APS. Most of these studies did not report any thrombotic events or any increase in the titers or prevalence of APLs in APS patients following COVID-19 vaccination.…”
Section: Sars-cov-2 Vaccination Appears To Be Safe In Antiphospholipi...mentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, consideration should also be given to the role played by SARS-CoV-2 when evaluating the association between COVID-19 vaccines and the development of new-onset autoimmune diseases. [21][22][23]…”
mentioning
confidence: 99%